Dampak Stres Kerja dan Beban Kerja Terhadap Kinerja Pegawai - Rani Indah Safitri; Sofia Ulfa Eka Hadiyanti; Yulia Tri Kusumawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
Job stress and workload are two factors that frequently arise in modern organizational environments and have the potential to impact employee performance. Increased work demands and pressure in completing tasks can lead to psychological and physical conditions that impact employee work effectiveness. This study aims to analyze the effect of job stress and workload on employee performance at the Communication and Informatics Office of East Kalimantan Province. The study used a quantitative approach with a survey method of 94 respondents selected using simple random sampling techniques from a total population of 123 employees. Data were collected through a questionnaire using a Likert scale and analyzed using multiple linear regression analysis, while the research data were processed using SPSS (Statistical Product and Service Solutions) version 30. The results show that the effect of job stress on employee performance obtained a T-statistic value of −2.010 with a p-value of 0.047, therefore H1 is accepted. The effect of workload on employee performance obtained a T-statistic value of −2.306 with a p-value of 0.023, therefore H2 is accepted. Simultaneously, the effect of job stress and workload on employee performance obtained an F-statistic value of 4.671 with a p-value of 0.012, therefore H3 is accepted. In addition, the coefficient of determination (R²) value of 0.093 indicates that job stress and workload contribute 9.3% to the variation in employee performance.